The Sodium Chloride Cotransporter (NCC) and Epithelial Sodium Channel (ENaC) Associate - Mistry, Abinash C. (Biochem J, 2016)
The thiazide-sensitive sodium chloride cotransporter (NCC) and the Epithelial Sodium Channel (ENaC) are two of the most important determinants of salt balance and thus systemic blood pressure. Abnormalities in either result in profound changes in blood pressure. There is one segment of the nephron where these two sodium transporters are co-expressed, the second part of the Distal Convoluted Tubule. This is a key part of the aldosterone-sensitive distal nephron, the final regulator of salt handling in the kidney. Aldosterone is the key hormonal regulator for both of these proteins. Despite these shared regulators and co-expression in a key nephron segment, associations between these proteins have not been investigated. After confirming apical localization of these proteins, we demonstrated the presence of functional transport proteins and native association by Blue Native PAGE. Extensive co-immunoprecipitation experiments demonstrated a consistent interaction of NCC with alpha and gamma ENaC. Mammalian two-hybrid studies demonstrated direct binding of NCC to ENaC subunits. Fluorescence Resonance Energy Transfer and immunogold EM studies confirmed that these transport proteins are within appropriate proximity for direct binding. Additionally, we demonstrate that there are functional consequences of this interaction, with inhibition of NCC affecting ENaC function. This novel finding of an association between ENaC and NCC could alter our understanding of salt transport in the distal tubule.